Enhancing Patient Communication Through Health Professionals’ Digital Literacy - Monica G. Brînzac; Marius I. Ungureanu; Mara Bumbu; Cătălin O. Baba (Transylvanian Review of Administrative Sciences, 2024)
Digital health literacy has been defined as the ‘ability to seek, find, understand, and appraise health information from electronic sources and apply the knowledge gained to address or solve a health problem’ (Norman and Skinner, 2006). Health literacy and digital health literacy are essential in order to reach universal health coverage and to reform the processes of the healthcare systems (WHO, 2018). Healthcare professionals need to treat patients in a continuous evolving structure (WHO, 2013). The research question that guided the paper is ‘How can Romanian health professionals’ digital health literacy be used to improve communication with their patients?’. The aim of the study is to explore Romanian health professionals’ level of digital literacy, to identify how it can improve the communication with the patients. 20 interviews with resident and senior medical doctors, medical students and nurses were conducted. The interviews were audio recorded, transcribed and then stored as Word documents in a password-secured environment. From the data gathered in the interviews four major themes emerged: (a) digital health literacy; (b) communication with the patients; (c) improvements for the National Health Strategy 2014-2020; (d) time as a barrier in communication. Data was analyzed using thematic analysis through the MAXQDA2018 software.